ADVANCED SECOND LANGUAGE LEARNERS' PERCEPTION OF LEXICAL TONE CONTRASTS. Issue 1 (15th May 2018) - Pelzl, Eric; Lau, Ellen F.; Guo, Taomei; DeKeyser, Robert
Abstract: It is commonly believed that second language (L2) acquisition of lexical tones presents a major challenge for learners from nontonal language backgrounds. This belief is somewhat at odds with research that consistently shows beginning learners making quick gains through focused tone training, as well as research showing advanced learners achieving near-native performance in tone identification tasks. However, other long-term difficulties related to L2 tone perception may persist, given the additional demands of word recognition and the effects of context. In the current study, we used behavioral and event-related potential (ERP) experiments to test whether perception of Mandarin tones is difficult for advanced L2 learners in isolated syllables, disyllabic words in isolation, and disyllabic words in sentences. Stimuli were more naturalistic and challenging than in previous research. While L2 learners excelled at tone identification in isolated syllables, they performed with very low accuracy in rejecting disyllabic tonal nonwords in isolation and in sentences. We also report ERP data from critical mismatching words in sentences; while L2 listeners showed no significant differences in responses in any condition, trends were not inconsistent with the overall pattern in behavioral results of less sensitivity to tone mismatches than to semantic or segmental mismatches. We interpret these results as evidence that Mandarin tones are in fact difficult for advanced L2 learners. However, the difficulty is not due primarily to an inability to perceive tones phonetically, but instead is driven by the need to process tones lexically, especially in multisyllable words.